Meta images on television and vanguard: Globo network television and MTV's art-breaks (RuMoRes, 2011)
From discussions about paleo and neo-television pointed by Umberto Eco, Francesco Casetti and Roger Odin, we intend to inquire about the interruption ability of television metaimages, analyzing Rede Globo’s and MTV’s art-breaks. The association of artbreaks poetics with some aesthetical recourses used by avantgarde artists from the beginning of XX century, as their narrative and non-narrative possibilities, base the argument. Umberto Eco, John Caldwell, Anika Schoemann and Flávio Cauduro will be the authors analyzed.